Handling newborn monkeys alters later exploratory, cognitive, and social behaviors. (February 2019) - Simpson, Elizabeth A.; Sclafani, Valentina; Paukner, Annika; Kaburu, Stefano S.K.; Suomi, Stephen J.; Ferrari, Pier F.
Highlights: Touch improves infant health, but little is known about behavioral effects of touch. We explored the influence of neonatal social touch on rhesus macaque monkeys. Newborns who received extra handling responded more positively to novelty. Higher rates of touch were associated with better cognitive and social development. Neonatal touch may broadly support infants' development. Abstract: Touch is one of the first senses to develop and one of the earliest modalities for infant-caregiver communication. While studies have explored the benefits of infant touch in terms of physical health and growth, the effects of social touch on infant behavior are relatively unexplored. Here, we investigated the influence of neonatal handling on a variety of domains, including memory, novelty seeking, and social interest, in infant monkeys ( Macaca mulatta ; n  = 48) from 2 to 12 weeks of age. Neonates were randomly assigned to receive extra holding, with or without accompanying face-to-face interactions. Extra-handled infants, compared to standard-reared infants, exhibited less stress-related behavior and more locomotion around a novel environment, faster approach of novel objects, better working memory, and less fear towards a novel social partner. In sum, infants who received more tactile stimulation in the neonatal period subsequently demonstrated more advanced motor, social, and cognitive skills—particularly in contexts involving exploration of novelty—in the first three months of life. These data suggest that social touch may support behavioral development, offering promising possibilities for designing future early interventions, particularly for infants who are at heightened risk for social disorders.